Rural labor migration, characteristics, and employment patterns: a study based on China's agricultural census - Tuan, Francis; Somwaru, Agapi; Diao, Xinshen (International Food Policy Research Institute, 2000)
Continued industrialization in China and increase in its agricultural productivity imply that surplus rural workers will to be attracted into non-agricultural production activities and, consequently, will have the opportunity to increase their off-farm income. Studying the structure of the rural labor force and its characteristics is important for evaluating its migration potential into non-agricultural sectors. This study examines the rural labor market in China exclusively based on China's first national agricultural census. We analyzed the demographic characteristics of the rural labor force and their association with the type of employment, place of work, and labor migration. Furthermore, we investigated demographic distributions of rural labor force and attempted to capture their relation with the distribution of other resources especially land availability or land constraints. We finally applied a generalized polytomous logit technique to analyze the patterns of rural labor employment and forecast rural migration. In this framework, we related rural labor migration with demographic characteristics, types of occupation, place of work, geographic characteristics, and various economic development indicators.